Emotional valence and spatial congruency differentially modulate crossmodal processing: an fMRI study - Wolf, Dhana; Schock, Lisa; Bhavsar, Saurabh; Demenescu, Liliana R.; Sturm, Walter; Mathiak, Klaus (Frontiers in Human Neuroscience, 2014)
Salient exogenous stimuli modulate attentional processes and lead to attention shifts - even across modalities and at a pre-attentive level. Stimulus properties such as hemispheric laterality and emotional valence influence processing, but their specific interaction in audio-visual attention paradigms remains ambiguous. We conducted an fMRI experiment to investigate the interaction of supramodal spatial congruency, emotional salience, and stimulus presentation side on neural processes of attention modulation. Emotionally neutral auditory deviants were presented in a dichotic listening oddball design. Simultaneously, visual target stimuli (schematic faces) were presented, which displayed either a negative, or a positive emotion. These targets were presented in the left or in the right visual field and were either spatially congruent (valid) or incongruent (invalid) with the concurrent deviant auditory stimuli. According to our expectation we observed that deviant stimuli serve as attention-directing cues for visual target stimuli. Region-of-interest analyses suggested differential effects of stimulus valence and spatial presentation on the hemodynamic response in bilateral auditory cortices. These results underline the importance of valence and presentation side for attention guidance by deviant sound events and may hint at a hemispheric specialization for valence and attention processing.